Hubungan Motivasi, Disiplin dan Komunikasi Internal dengan Prestasi Belajar Taruna Balai Pendidikan dan Pelatihan Transportasi Darat Palembang - Arlieny Arlieny; Agusta Pinta Kurnia Rizky; Tri Suyantiningsih (The Asia Pacific Journal Of Management Studies, 2020)
To improve the performance of cadets, no less importantly, the discipline of the cadets themselves. Discipline affect academic achievement as the essence of discipline is the attitude and actions to adjust to the discipline or organization in this school/college. Realization of discipline will affect the implementation of all learning activities is expected. The population in this study were all cadets in the Diploma Program D III LLASDP. Sampling technique using a random sampling. There motivation Relationships with Youth Achievement, because the t value significant There is no relationship Discipline with Youth Achievement because t values significant. There Relations Internal Communication with Youth Achievement, because the t value significant. After looking at the relationship of each variable the achievement Youth Diploma motivated by the Internal Motivation and Communication awarded to cadets that factor increasing the Academic Achievement School need to increase the factors of all variables.